Hibiscus sabdariffa on Fibroblast Growth Factor 21 (FGF21) on Diabetes Mellitus Type 2 Patients - Haque, Sumayya Nuri Fuadana Aulia Ul; Bayani, Gulshan Fahmi El (International Journal Labs, 2023)
FGF21 has a role in modulating the uptake of macronutrients in the body. It is produced by the liver in response to high carbohydrate intake and acts as a signal to the brain to reduce carbohydrate intake. Liver is the main site for FGF21 production under the regulation of Unfolding Protein Response (UPR) in hepatocytes. FGF21 has an important role in regulating peripheral glucose tolerance as well as lipid metabolism. FGF21 expression in the liver depends on the PKR-like ER kinase (PERK)–eukaryotic initiation factor 2? (eIF2?)–activating transcription factor 4 (ATF4) pathway. FGF21 can regulate the expression of glucose transporter 1, and increase glucose uptake. In addition, research shows that FGF21 can reduce blood sugar levels and also body weight in mice1. FGF21 can also increase insulin sensitivity by suppressing hepatic glucose production and increasing hepatic glycogen content, so that this can improve systemic glucose intolerance and insulin resistance. The researchers attempted to discover the influence of Hibiscus sadariffa on FGF21 on Diabetes mellitus type 2 patients. The method used was literature review with data generated from various sources such as Google Scholar, Scopus, and Pubmed. FGF21 has an effect on the function of ? and ß cells in the pancreas organ. In the islets of the pancreatic organs of rats with DM, administration of FGF21 increased insulin levels, induced insulin secretion, and inhibited glucagon secretion.